2023
DOI: 10.3390/risks11020040
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Determinants of Islamic Mobile FinTech Service Acceptance: A Modified UTAUT2 Approach

Abstract: Financial technology (FinTech) is leading a worldwide revolution to increase financial access. Bangladesh’s financial sector is entering a new era of innovation due to the country’s rapid embrace of financial technology. Mobile FinTech service (MFS) providers achieve unattainable economic peaks every year. The growth of conventional banks’ MFS is significant. However, Islamic banks have a good market share but cannot attract more customers to use the Islamic MFS. This study aimed to determine the factors influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 50 publications
3
9
0
1
Order By: Relevance
“…In addition, performance expectancy has a significant impact on users' behavioral intention and this result is validated by prior research findings (Rabaa'i, 2021;Alkhwaldi et al, 2022;Kurniasari et al, 2023), but contradictory results have also been reported (Hassan et al, 2023;Ramprakash et al, 2023). Furthermore, it was found that performance expectancy significantly influences customer satisfaction, and our finding is supported by Chao (2019) and contradicted by Esawe (2022).…”
Section: Findings and Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, performance expectancy has a significant impact on users' behavioral intention and this result is validated by prior research findings (Rabaa'i, 2021;Alkhwaldi et al, 2022;Kurniasari et al, 2023), but contradictory results have also been reported (Hassan et al, 2023;Ramprakash et al, 2023). Furthermore, it was found that performance expectancy significantly influences customer satisfaction, and our finding is supported by Chao (2019) and contradicted by Esawe (2022).…”
Section: Findings and Discussionsupporting
confidence: 87%
“…In addition, it was identified that effort expectancy is a significant determinant that affects consumers’ behavioral intention. Rubaia and Pria (2022), Rabaa’i (2021) and Kurniasari et al (2023) validate our findings, but Hassan et al (2023) and Hassan et al (2022) contradict our findings. Moreover, it was uncovered that there is a significant impact of effort expectancy on customer satisfaction, which is supported by past studies of Chao (2019) and Esawe (2022).…”
Section: Findings and Discussionsupporting
confidence: 84%
“…Perceived Credibility significantly influences the adoption of digital sharia banking services by customers, in line with previous research (Hassan et al, 2023). As sharia banking digital services are relatively new compared to conventional banking, credibility becomes vital for customers due to its relationship with transaction risks.…”
Section: Discussionsupporting
confidence: 81%
“…The UTAUT2 paradigm is far more pertinent when considering individual consumers and how well they accept technology while using it to access internet services. The adoption of mobile FinTech [30], mobile banking [31], and mobile payment [32] [27], [28], for example, have all been found to be better explained by the UTAUT2 model, which connects a variety of technological and behavioral elements. This investigation follows the DL&ML model, the TAM, and UTAUT2 [33] theories as the conceptual model for examining the student adoption of video recordings within the subject Introduction to Databases Practicum course.…”
Section: Methodsmentioning
confidence: 99%